Consultation in Neurourology A Practical Evidence-Based Guide - Corcos, Jacques (Springer International Publishing, 2018)
This book is aimed to bring the reader into the heart of the action of any health professional consulted for a patient with a neurogenic bladder (NB). Extensive textbooks of the NB exist but there is a lack of an actual practical guide for diagnosis and management of patients suffering from NB. This book provides a single source of information on consultation in neurourology. The text covers both urinary incontinence and retention resulting from NB dysfunction. The book also discusses complications of NB which include urinary tract infections, hydronephrosis, renal failure or autonomic dysreflexia. Sections address these clinical issues faced by physicians. This book provides a useful guide with comprehensive and practical instructions for all practitioners dealing with NB in their day-to-day clinical practice. It will serve as a valuable resource for those with a special interest in NB. The book reviews new data about diagnostic and management options. It also provides a concise yet comprehensive summary of the current NB guidelines from different societies. All chapters include the most up to date scientific and clinical information with the relevant level of clinical evidence and grade of recommendation.